Fabrication of Photofunctional Nanoporous Membrane and Its Photoinactivation Effect of Vesicular Stomatitis Virus. (28th September 2011) - Wang, Kang-Kyun; Kim, Bong-Jin; Ko, Si-Hwan; Choi, Dong Hoon; Kim, Yong-Rok
Abstract : Fabrication and photophysical study of photofunctional nanoporous alumina membrane (PNAM) were performed, and its application of photodynamic antimicrobial chemotherapy (PACT) was investigated. Nanoporous alumina membrane (NAM) was fabricated by two-step aluminium anodic oxidation process. Surface of the fabricated NAM was modified with organo-silane agent to induce covalent bonding between NAM and a photosensitizer (PtCP: [5, 10, 15-triphenyl-20-(4-methoxycarbonylphenyl)-porphyrin] platinum). PtCP was covalently bonded to the surface of the modified NAM by nucleophilic acyl substitution reaction process. The morphology and the photophysical properties of the fabricated PNAM were confirmed with field emission scanning electron microscope (FE-SEM), steady-state spectroscopies, and nanosecond laser-induced time-resolved spectroscopy. For the efficacy study of PNAM in PACT, an enveloped animal virus, vesicular stomatitis virus (VSV), was utilized as a target organism. Antiviral effect of the PNAM-PACT was measured by the extent of suppression of plaque-forming units (PFU) after the light irradiation. In the cultures inoculated with PACT-treated VSV, the suppression of PFU was prominent, which demonstrates that PNAM is a potential bio clean-up tool.